Species Diversity and Seasonal Abundance of Stomoxyinae (Diptera: Muscidae) and Tabanid Flies (Diptera: Tabanidae) on a Beef Cattle and a Buffalo Farm in Nakhon Si Thammarat Province, Southern Thailand - Yotsapat Phetcharat; Tuempong Wongtawan; Punpichaya Fungwithaya; Jens Amendt; Narin Sontigun (My University, 2024)
This study investigated species diversity and seasonal abundance of Stomoxyinae and tabanid flies, which are significant pests and vectors of animal pathogens, on a beef cattle and a buffalo farm in Nakhon Si Thammarat province, southern Thailand. During a one-year period from December 2020 to November 2021, flies were collected using Nzi traps from 6 a.m. to 6 p.m. over three consecutive days each month, resulting in the capture of 1912 biting flies, representing seven Stomoxyinae and nine tabanid species. The five most prevalent species were Tabanus megalops, Haematobia irritans exigua, Stomoxys calcitrans, Stomoxys indicus, and Stomoxys uruma. Fly density was notably higher on the beef cattle farm compared to the buffalo farm, with most species peaking during the rainy season, except for H. i. exigua, which was more abundant during the dry season. This study also examined the influence of temperature, relative humidity, and rainfall on fly density, revealing species-specific patterns. These findings offer updated insights into species diversity and seasonal trends, providing critical baseline data essential for the development of effective control strategies aimed at mitigating the impact of these flies on livestock health.
Keywords: Haematobia irritans; Exigua; Wet season; Dry season; Stable fly; Forensic Entomology and Diptera Studies